Sulfide composite solid electrolyte and preparation method thereof

By mixing Nifes3 composite nanoparticles and introducing nickel and iron in sulfur -solid electrolytes, the lithium ion conductivity and reduction of interface resistance have been improved, and the problem of low vulcosine solid electrolyte conductivity and large interface resistance, significantly improved improvement, significantly improved improvement The performance of the all -solid lithium battery.

CN119381519APending Publication Date: 2025-01-28WANXIANG 123 CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411511625.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The existing sulfide solid electrolytes have low lithium ion conductivity and large interface resistance at room temperature, which limits the development of all-solid lithium batteries.

Method used

By mixing the modified sulfide positive material NIFES3 composite nanoparticles in the solid -state electrolyte, nickel and iron and iron are introduced in the electrolyte to increase the proportion of glass -state phases and reduce the interface contact resistance.

Benefits of technology

The lithium ion conductivity of the solid electrolyte of sulfide is significantly improved, the internal resistance of the battery is reduced, the composition of the SEI membrane is improved, and the power characteristics and cycle life of the solid battery are improved.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of solid-state batteries, in particular to sulfide composite solid electrolyte and a preparation method thereof. According to the preparation method of the high-performance glassy state sulfide solid electrolyte, a modified sulfide positive electrode material is doped in the sulfide solid electrolyte, and nickel and iron elements are introduced, so that the proportion of a glassy state phase in the sulfide solid electrolyte is increased, and the lithium ion conductivity of the sulfide solid electrolyte is remarkably improved; the interface contact resistance is reduced, the composition of the SEI film is improved, and the power characteristic and the cycle life of the solid battery are improved. Acrylate has the characteristics of stable and excellent adhesive force, good lithium ion transmission characteristic, good elasticity, good flame retardance and the like, so that the sulfide solid electrolyte has a viscous surface, the interface contact resistance is reduced, meanwhile, the safety of a battery adopting the sulfide composite solid electrolyte is improved, and the combustible risk is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of solid-state batteries, and in particular to a sulfide composite solid electrolyte and a preparation method thereof. Background Art

[0002] With the continuous improvement of living standards, people have put forward higher requirements for energy storage equipment. Lithium batteries have the advantages of high output power, high energy density, long service life, high average output voltage, low self-discharge, no memory effect, fast charge and discharge, excellent cycle performance and no environmental pollution. They have been widely used in daily life and have become the first choice for rechargeable power sources for portable electronic products today. They are also considered to be the most competitive automotive power batteries. Lithium batteries are divided into liquid lithium batteries and solid lithium batteries. Among them, liquid lithium batteries contain a large amount of flammable and volatile organic electrolytes. Under the conditions of overcharge, overdischarge and high temperature, they are prone to cause safety problems such as fire, which arouses people's concerns. Solid-state lithium batteries refer to lithium batteries in which all units of the battery, including the positive electrode, negative electrode and electrolyte, are made of solid materials. They have incomparable safety of liquid lithium batteries and are expected to completely eliminate safety hazards during use, which is more in line with the future development needs of electric vehicles and large-scale energy storage. Therefore, all-solid-state lithium batteries using solid electrolytes are candidate materials for the next generation of high-energy density batteries. The development of high-performance solid electrolytes is the key to realizing all-solid-state lithium batteries.

[0003] Solid electrolytes can be mainly divided into two categories: inorganic solid electrolytes and polymer solid electrolytes. Polymer electrolytes have disadvantages such as low room temperature ionic conductivity, narrow electrochemical window, and poor high temperature stability, which cannot meet the requirements of use. More conductive and durable electrolyte materials are conducive to the manufacture of high-power and high-safety energy storage systems. Recently, solid electrolytes represented by sulfides have high energy density and safety, and only lithium ions move inside the electrolyte during charging and discharging, avoiding unnecessary side reactions caused by anion movement, and meeting the technical requirements of long life, becoming a hot spot in industry research. However, there are still many technical challenges, such as low lithium ion conductivity and large interface resistance at room temperature, which have become the main bottlenecks restricting development.

[0004] The scheme with application number CN202080008256.0 discloses "sulfide solid electrolyte and its manufacturing method". By optimizing the preparation method, a sulfide solid electrolyte with small particle size and low specific surface area and an electrode mixture, slurry and battery using the sulfide solid electrolyte are provided. By suppressing the reaction area between sulfide and moisture in the air, the generation of hydrogen sulfide gas and the decrease in conductivity are avoided. However, the technical improvement effect on conductivity is limited; the patent with application number CN202110382390.3 discloses "a high air stability solid electrolyte and solid-state battery and its preparation method". By doping soft acid metals into the solid electrolyte, on the one hand, the ionic conductivity of the solid electrolyte is improved; on the other hand, the binding property with sulfur is improved, thereby improving the air stability of the solid electrolyte. However, new elements with potential toxicity are introduced, which has certain technical limitations. Summary of the invention

[0005] The present invention proposes a sulfide composite solid electrolyte and a preparation method thereof. By doping a modified sulfide positive electrode material into the sulfide solid electrolyte and introducing nickel and iron elements, the proportion of a glassy phase in the sulfide composite solid electrolyte is increased, thereby significantly improving the lithium ion conductivity of the sulfide solid electrolyte, reducing the interface contact resistance, and improving the composition of the SEI film, thereby improving the power characteristics and cycle life of the solid battery.

[0006] In a first aspect, the present application provides a method for preparing a sulfide composite solid electrolyte:

[0007] A method for preparing a sulfide composite solid electrolyte comprises the following preparation steps:

[0008] a) dissolving a nickel-containing compound, a soluble iron salt and thiourea in an alkaline solvent in a mass ratio of 30-50:15-25:50-70 to obtain a suspension having a mass fraction of 1.5-3.5 wt % of the total solute; then reacting the suspension at a temperature of 180-240° C. for 12-16 hours, washing and drying to prepare NiFeS3 composite nanoparticles;

[0009] b) using Li2S, lithium halide, P2S5 and NiFeS3 nanoparticles prepared in step a) as raw materials, and ball milling them according to the molar ratio of 7.0-9.5:1.0-2.0:2.5-4.0:0.5-1.6 to obtain a glassy sulfide solid electrolyte;

[0010] c) placing the glassy sulfide solid electrolyte prepared in step b) between two acrylic ester film layers and pressing them into sheets to obtain a composite solid electrolyte.

[0011] Among them, lithium halide can improve the mechanical and chemical stability of SEI film in SEI film, and doping NiFeS3 composite nanoparticles can accelerate the diffusion of lithium ions and the evolution of intermediate phases in sulfide solid electrolytes, significantly improve the lithium ion conductivity of electrolytes, and reduce the internal resistance of batteries; the introduced Ni and Fe elements are not potentially toxic. Among them, NiS2 nanoparticles are a typical pyrite-type structure compound with a conductivity of about 55S / cm and can provide a high theoretical specific capacity of about 870mAh / g; FeS has a specific electron transfer ability and a low band gap. The NiFeS3 composite nanoparticles prepared by the composite of the two have the advantages of both, which can effectively improve the interface resistance between sulfide solid electrolyte particles and reduce the internal resistance of batteries.

[0012] Acrylate has excellent and stable adhesion, good lithium ion transmission characteristics, good elasticity, good flame retardancy, etc., which makes the sulfide solid electrolyte have a sticky surface, reduces the interface contact resistance, and improves the safety of batteries using sulfide composite solid electrolytes, reducing the flammability risk of batteries. If the thickness of the acrylate is too low, the viscosity effect is not obvious, and if the thickness is too large, the interface internal resistance will increase, which is not conducive to the performance of the battery.

[0013] Furthermore, the nickel-containing compound is at least one of nickel sulfate, nickel chloride, nickel sulfamate, nickel bromide, and nickelous hydroxide; and the soluble iron salt is at least one of ferric nitrate, ferric chloride, and ferric sulfate.

[0014] Furthermore, the lithium halide is at least one of lithium iodide, lithium chloride and lithium bromide.

[0015] Furthermore, the nickel-containing compound is nickel nitrate, the soluble iron salt is iron nitrate, and the lithium halide is lithium iodide.

[0016] Furthermore, the thickness of the acrylic ester film layer is 2-7 μm; the thickness of the glassy sulfide solid electrolyte layer is 30-150 μm.

[0017] Furthermore, the alkaline solvent is any one of ethanolamine, triethylamine and tetramethylethylenediamine.

[0018] Furthermore, in the step b), the ball milling conditions are as follows: a ball milling speed of 550-650 rpm, a ball milling time of 20-40 hours, and the balls are stopped for cooling for 20-40 minutes every 100-150 minutes of ball milling.

[0019] Furthermore, in the step a), the drying condition is 65-85° C. and the drying time is 8-12 hours.

[0020] Furthermore, in the step b), the ball milling is performed in an environment where the oxygen content is lower than 10 ppm.

[0021] Furthermore, in the step c), the pressing is performed at 100-500 standard atmospheric pressure to form tablets.

[0022] In a second aspect, the present application provides a sulfide composite solid electrolyte:

[0023] A sulfide composite solid electrolyte is prepared by using the preparation method of a sulfide composite solid electrolyte described in the present application.

[0024] Beneficial effects:

[0025] The present invention proposes a high-performance glassy sulfide solid electrolyte and a preparation method thereof. By doping a modified sulfide positive electrode material into the sulfide solid electrolyte and introducing nickel and iron elements, the proportion of the glassy phase in the sulfide solid electrolyte is increased, thereby significantly improving the lithium ion conductivity of the sulfide solid electrolyte, reducing the interface contact resistance, and improving the composition of the SEI film, thereby improving the power characteristics and cycle life of the solid battery.

[0026] Acrylates have stable and excellent adhesion, good lithium ion transmission properties, good elasticity, good flame retardancy, etc., which make the sulfide solid electrolyte have a sticky surface, reduce the interfacial contact resistance, and at the same time improve the safety of batteries using sulfide composite solid electrolytes and reduce the risk of flammability. DETAILED DESCRIPTION

[0027] In order to make the technical solution of the present invention clearer, the present invention is further described in detail with reference to specific embodiments.

[0028] If no specific techniques or conditions are specified in the examples, the techniques or conditions described in the literature in the field or the product instructions are used. All reagents or instruments without manufacturer specified are conventional products that can be purchased through regular channels.

[0029] Example 1

[0030] A preparation method of a sulfide composite solid electrolyte comprises the following steps:

[0031] a. nickel nitrate Ni(NO3)·6H2O (purity>98.5%), iron nitrate Fe(NO3)·9H2O (purity greater than 99.0%) and thiourea CH4N2S were dissolved in ethanolamine (purity greater than 99.0%) solvent in a mass ratio of 45:17:61, with a total solute mass fraction of 2.5%, and stirred at 200 rpm for 35 minutes at room temperature to obtain a uniformly dispersed suspension, and then the suspension was transferred into a polytetrafluoroethylene-lined stainless steel hydrothermal autoclave, and a solvent thermal reaction was carried out at 220°C for 14 hours. The resulting product was collected and washed 4 times with distilled water and anhydrous ethanol respectively, and dried overnight in a vacuum oven at 70°C to obtain NiFeS3 composite nanoparticles;

[0032] b. In an environment where the water and oxygen content are all lower than 10ppm, Li2S (purity>99.9%), LiI (purity>99%), P2S5 (purity>99%) and the NiFeS3 nanoparticles prepared in step a are used as raw materials and added into a high-energy vibration ball mill according to a molar ratio of 8.3:1.3:2.9:1.2, and ball milled for 37 hours at room temperature to obtain a Li2S-LiI-P2S5-NiFeS3 glassy sulfide solid electrolyte, wherein the ball milling speed is 600 rpm, and in order to avoid temperature rise during the ball milling process, the ball milling is stopped and cooled for 35 minutes every 120 minutes;

[0033] c. The obtained Li2S-LiI-P2S5-NiFeS3 glassy sulfide solid electrolyte powder was placed in a stainless steel mold, an acrylic film layer was placed on the bottom of the mold in advance, and then another piece of the same acrylic film layer was placed on the top of the powder, and pressed into a sheet at 350 standard atmospheric pressure to obtain a Li2S-LiI-P2S5-NiFeS3 composite solid electrolyte coated with acrylic film layers on both sides. The thickness of the Li2S-LiI-P2S5-NiFeS3 layer is 40μm, and the thickness of the polyvinyl acetate film is 4μm.

[0034] Example 2, preparation of a sulfide composite solid electrolyte:

[0035] Compared with Example 1, in Example 2, nickel nitrate Ni(NO3)·6H2O (purity>98.5%), iron nitrate Fe(NO3)·9H2O (purity greater than 99.0%) and thiourea CH4N2S are dissolved in ethanolamine (purity greater than 99.0%) solvent in a mass ratio of 50:15:50, and the mass fraction of the total solute is 3.5%. The mixture is stirred at 250 rpm for 20 minutes at room temperature to obtain a uniformly dispersed suspension, and then the suspension is transferred into a polytetrafluoroethylene-lined stainless steel hydrothermal reactor, and a solvent thermal reaction is carried out at 240°C for 12 hours. The obtained product is collected and washed 5 times with distilled water and anhydrous ethanol respectively, and dried overnight at 85°C in a vacuum oven to obtain NiFeS3 composite nanoparticles. The remaining conditions are the same as those in Example 1.

[0036] Example 3, preparation of a sulfide composite solid electrolyte:

[0037] Compared with Example 1, the preparation conditions of step b in Example 3 are: in an environment where the water and oxygen content are all lower than 10ppm, Li2S (purity>99.9%), LiI (purity>99%), P2S5 (purity>99%) and NiFeS3 nanoparticles prepared in step a are added as raw materials in a high-energy vibration ball mill according to a molar ratio of 9.5:1.0:4.0:0.5, and ball milled for 20 hours at room temperature to obtain Li2S-LiI-P2S5-NiFeS3 glassy sulfide solid electrolyte, wherein the ball milling speed is 650 rpm, and in order to avoid the temperature rising during the ball milling process, the ball milling is stopped for 40 minutes every 150 minutes to cool. The remaining conditions are the same as those in Example 1.

[0038] Example 4, preparation of a sulfide composite solid electrolyte:

[0039] Compared with Example 1, in Example 4, the thickness of the Li2S-LiI-P2S5-NiFeS3 layer is 150 μm, and the thickness of the acrylic acid is 7 μm. The two are pressed into sheets at 500 standard atmospheres, and the other conditions are the same as in Example 1.

[0040] Example 5, preparation of a sulfide composite solid electrolyte:

[0041] Compared with Example 1, in Example 5, nickel nitrate is replaced by nickel sulfate, ferric nitrate is replaced by ferric chloride; LiI is replaced by lithium chloride, and the remaining conditions are the same as those in Example 1.

[0042] Comparative Example 1, preparation of a sulfide composite solid electrolyte:

[0043] Compared with Example 1, the sulfide composite solid electrolyte in Comparative Example 1 does not contain NiFeS3 composite nanoparticles, and the other conditions are the same as those in Example 1.

[0044] Comparative Example 2, preparation of a sulfide composite solid electrolyte:

[0045] Compared with Example 1, the sulfide composite solid electrolyte in Comparative Example 2 does not contain LiI, and the other conditions are the same as those in Example 1.

[0046] Comparative Example 3, preparation of a sulfide composite solid electrolyte:

[0047] Compared with Example 1, in Comparative Example 3, acrylic acid is not coated on both sides of the sulfide composite solid electrolyte, and the remaining conditions are the same as those in Example 1.

[0048] Comparative Example 4, preparation of a sulfide composite solid electrolyte:

[0049] Compared with Example 1, in Comparative Example 4, the thickness of the Li2S-LiI-P2S5-NiFeS3 layer is 200 μm, and the thickness of the acrylic acid is 10 μm. The two are pressed into sheets at 50 standard atmospheres, and the other conditions are the same as in Example 1.

[0050] Comparative Example 5, preparation of a sulfide composite solid electrolyte:

[0051] Compared with Example 1, in Comparative Example 5, the NiFeS3 nanoparticles are replaced by FeS nanoparticles in equal amounts, and the other conditions are the same as those in Example 1.

[0052] Comparative Example 6, preparation of a sulfide composite solid electrolyte:

[0053] Compared with Example 1, the NiFeS3 nanoparticles in Comparative Example 6 are replaced by NiS2 nanoparticles in equal amounts, and the other conditions are the same as those in Example 1.

[0054] Performance Evaluation

[0055] Two metal lithium sheets were placed on both sides of the sulfide composite solid electrolyte, and after pressing at 100 standard atmospheres, a 2032-type button-type symmetrical all-solid battery was prepared. The internal resistance of the battery was tested using the EIS at 30°C, with an applied voltage amplitude of 5-10mV and a frequency range of 0.1-100000HZ. Before the EIS test, the battery needed to be left to stand for 1.5 hours to reach an electrochemically stable state. At 30°C, within a voltage range of 2.0-3.1V, with a charge and discharge rate of 0.1C, a cycle test was performed. When the battery capacity retention rate dropped to 80% of the discharge capacity in the first week, it was considered to have reached the end of its life and the experiment was terminated. The experimental data are shown in Table 1.

[0056] Table 1. Comparison of performance of sulfide solid electrolytes prepared under different conditions

[0057] Internal resistance(Ω) Cycle life (weeks) Example 1 56.4 657 Example 2 57.8 648 Example 3 58.1 642 Example 4 56.9 650 Example 5 57.3 653 Comparative Example 1 89.2 536 Comparative Example 2 70.7 549 Comparative Example 3 75.1 537 Comparative Example 4 74.2 556 Comparative Example 5 76.9 539 Comparative Example 6 74.5 524

[0058] The specific results are shown in Table 1. Combined with Examples 1-5, it can be seen that within the specified technical range, the lithium ion conductivity and cycle life of the prepared sulfide composite solid electrolyte have been significantly improved, among which Example 1 has the best effect; combined with Example 1 and Comparative Examples 1, 2, 5, 6, it is shown that after doping NiFeS3 composite nanoparticles and LiI with a larger halogen atomic radius inside the sulfide solid electrolyte, the internal resistance and cycle life have been significantly improved. The main mechanism is that NiFeS3 composite nanoparticles and LiI improve the lithium ion transmission pathway, diffusion rate and evolution of the intermediate phase inside the solid electrolyte, and reduce lithium ion transmission and interface internal resistance. Combined with Example 1 and Comparative Examples 3 and 4, it is found that coating an acrylic film layer on both sides of the sulfide solid electrolyte layer can increase the bonding force between the electrolyte and the pole piece, reduce the interface contact impedance, and match lithium iodide with a larger halogen atomic radius, which is more conducive to the conduction of electrons, effectively reduce the internal resistance of the battery, and extend the battery cycle life. When the thickness of the solid electrolyte layer and the acrylic layer is too high, it will cause the internal resistance of the battery to increase.

[0059] Compared with the existing technical solutions, the present invention proposes a high-performance glassy sulfide solid electrolyte and a preparation method thereof. By doping modified sulfide positive electrode materials into the sulfide solid electrolyte, the lithium ion conductivity of the sulfide solid electrolyte is significantly improved, the interface contact resistance is reduced, and the composition of the SEI film is improved, thereby improving the power characteristics and cycle life of the solid battery, which is conducive to the development of high-performance solid batteries.

[0060] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A method for preparing a sulfide composite solid electrolyte, characterized in that: The method comprises the following preparation steps: a) dissolving a nickel-containing compound, a soluble iron salt and thiourea in an alkaline solvent in a mass ratio of 30-50:15-25:50-70 to obtain a suspension having a mass fraction of 1.5-3.5 wt % of the total solute; then reacting the suspension at a temperature of 180-240° C. for 12-16 hours, washing and drying to prepare NiFeS3 composite nanoparticles; b) using Li2S, lithium halide, P2S5 and NiFeS3 nanoparticles prepared in step a) as raw materials, and ball milling them according to the molar ratio of 7.0-9.5:1.0-2.0:2.5-4.0:0.5-1.6 to obtain a glassy sulfide solid electrolyte; c) placing the glassy sulfide solid electrolyte prepared in step b) between two acrylic ester film layers and pressing them into sheets to obtain a composite solid electrolyte.

2. The method for preparing a sulfide composite solid electrolyte according to claim 1, characterized in that: The nickel-containing compound is at least one of nickel sulfate, nickel chloride, nickel sulfamate, nickel bromide, and nickelous hydroxide; the soluble iron salt is at least one of ferric nitrate, ferric chloride, and ferric sulfate.

3. The method for preparing a sulfide composite solid electrolyte according to claim 1, characterized in that: The lithium halide is at least one of lithium iodide, lithium chloride and lithium bromide.

4. The method for preparing a sulfide composite solid electrolyte according to claim 1, characterized in that: The nickel-containing compound is nickel nitrate, the soluble iron salt is iron nitrate, and the lithium halide is lithium iodide.

5. The method for preparing a sulfide composite solid electrolyte according to claim 1, characterized in that: The thickness of the acrylic ester film layer is 2-7 μm; the thickness of the glassy sulfide solid electrolyte layer is 30-150 μm.

6. The method for preparing a sulfide composite solid electrolyte according to claim 1, characterized in that: The alkaline solvent is any one of ethanolamine, triethylamine and tetramethylethylenediamine.

7. The method for preparing a sulfide composite solid electrolyte according to claim 1, characterized in that: In the step a), the drying condition is 65-85° C. and the drying time is 8-12 hours.

8. The method for preparing a sulfide composite solid electrolyte according to claim 1, characterized in that: In the step b), the ball milling conditions are as follows: a ball milling speed of 550-650 rpm, a ball milling time of 20-40 hours, and the balls are stopped for cooling for 20-40 minutes after every 100-150 minutes of ball milling; and the ball milling is carried out in an environment where the oxygen content is less than 10 ppm.

9. The method for preparing a sulfide composite solid electrolyte according to claim 1, characterized in that: In the step c), the pressing is performed at 100-500 standard atmospheres to form tablets.

10. A sulfide composite solid electrolyte, characterized in that: The sulfide composite solid electrolyte is prepared by the preparation method of any one of claims 1 to 9.

Citation Information

Patent Citations

  • Nanocrystalline sulfide solid electrolyte with high air stability, preparation method thereof, solid-state battery and preparation method of solid-state battery

    CN113097560A

  • Sulfide solid electrolyte and production method thereof

    CN113348577A